Vitamin D and assisted reproductive treatment outcome: a prospective cohort study - Justin Chu; Ioannis Gallos; Aurelio Tobias; Lynne Robinson; Jackson Kirkman-Brown; Rima Dhillon-Smith; Hoda Harb; Abey Eapen; Madhurima Rajkhowa; Arri Coomarasamy (BMC, 2019)
Abstract Background Vitamin D deficiency has been associated with an increased risk of abnormal pregnancy implantation leading to obstetric complications such as pre-eclampsia and fetal growth restriction. However, the effect of vitamin D on reproductive treatment outcomes in couples undergoing assisted reproductive treatment is poorly understood. This study investigates the association between vitamin D and reproductive treatment outcomes in women undergoing assisted reproductive treatments? Methods A prospective cohort study conducted at a large tertiary teaching hospital, United Kingdom. Five hundred women undergoing assisted reproductive treatment were recruited between September 2013 and September 2015. All participants had their serum vitamin D measured and their reproductive treatment outcomes collated. Women were categorised in to three groups: vitamin D replete (> 75 nmol/L), insufficient (50-75 nmol/L) and deficient (< 50 nmol/L) according to Endocrine Society guidance. The primary outcome was live birth. Secondary outcomes included biochemical pregnancy, clinical pregnancy and pregnancy loss rates. Results Vitamin D deficiency was found in 53.2% (266/500) of participants and vitamin D insufficiency was found in 30.8% (154/500) of participants. Only 16% (80/500) of women were vitamin D replete. The live birth rates for vitamin D deficient, insufficient and replete women were 23.2% (57/246), 27.0% (38/141) and 37.7% (29/77) respectively (p = 0.04). The respective live birth rates for vitamin D deficient, insufficient and replete women were 24.3, 27.1, 34.4% after adjustment for key prognostic factors (p = 0.25). Conclusions Vitamin D deficiency and insufficiency are common in women undergoing assisted reproductive treatments. The crude live birth rate achieved in women undergoing assisted reproductive treatments are associated with serum vitamin D, although statistical significance is lost when adjusting for important prognostic variables. Vitamin D deficiency could be an important condition to treat in women considering fertility treatment. A research trial to investigate the benefits of vitamin D deficiency treatment would test this hypothesis. Trial registration Clinicaltrials.gov - NCT02187146.